The Effect of Deposition Temperatures on the Structural and Optical Properties of CuZnS Thin Films - Layth A. Saleh; Ziad T. Khodair (Academic Science Journal)
The structural and optical characteristics of thin CuZnS films were examined in this research. The films were created utilizing the spin coating technique at different temperatures (200, 250 and 300 °C). According to XRD investigations, all compounds showed a polycrystalline structure with a hexagonal structure. The field emission scanning electron microscopy, surface morphology were investigated (FE-SEM). As the temperature is raised, the average particle size increases. The absorption spectra of CuZnS thin films showed that, for all samples, absorption increases as temperature rises for all samples. The optical characteristics of the material, including absorbance and absorbance coefficient, were investigated as well.